Power and Manipulative Function of Language: Critical Discourse Analysis of Utoh-Ezeajugh’s Our Wives Have Gone Mad Again (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This study investigates the intersection of power and manipulative function of language in Tracie Uto-Ezeajughi’s Our Wives Have Gone Mad Again using Critical Discourse Analysis (CDA) as the methodological approach. Drawing on the theoretical frameworks of Norman Fairclough the research explores how language serves as a tool for both maintaining and challenging power structures within patriarchal Nigerian societies. Fairclough’s three-dimensional model-textual analysis, discourse practice, and socio-cultural practice provides the basic tools for analyzing how characters use language to assert dominance, resist subjugation, and negotiate identity. The study adopts purposive sampling in selecting excerpts from the play. Specific dialogues and scenes that foreground power relations, gender dominance, and manipulative use of language were intentionally selected for analysis. The play reveals how one gender deploys language to reinforce gender hierarchies and control, and how the other gender subverts these manipulations through satire, interrogations, imperative and assertive speech. Through detailed textual and contextual analysis, the study demonstrates that language functions not merely as communication, but as a strategic instrument of power, resistance, and social change. The findings underscore the role of discourse in shaping gender relations and contributing to broader ideological struggles within postcolonial African settings.
Keywords: Power; manipulation; ideology; gender; oppression